2019
DOI: 10.1016/j.celrep.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nuclear TDP-43 Is Associated with Decondensation of LINE Retrotransposons

Abstract: Highlights d Nuclei without nuclear TDP-43 were sorted from postmortem FTD-ALS human brains d Loss of nuclear TDP-43 was associated with widespread transcriptome changes d Loss of nuclear TDP-43 was linked to chromatin decondensation at LINEs d Loss of nuclear TDP-43 enhanced LINE retrotransposition in vitro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
213
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(253 citation statements)
references
References 84 publications
12
213
2
2
Order By: Relevance
“…Moreover, the connection between TDP-43 and transposable elements has only recently been explored. While previous studies have linked TDP-43 to transposon binding in human cells and to transposon regulation in animal models (Chang and Dubnau, 2019;Krug et al, 2017;Li et al, 2015;Liu et al, 2019), we show that TDP-4-bound transposon transcripts are de-silenced in human cells and demonstrate that these same targets are de-silenced in a subset of human ALS patients. Additional mechanisms for transposon de-silencing in ALS patients with C9orf72 repeat expansions have been suggested (Pereira et al, 2018;Prudencio et al, 2017;Zhang et al, 2019), although we note that C9orf72 status was not strongly associated with the ALS-TE group in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, the connection between TDP-43 and transposable elements has only recently been explored. While previous studies have linked TDP-43 to transposon binding in human cells and to transposon regulation in animal models (Chang and Dubnau, 2019;Krug et al, 2017;Li et al, 2015;Liu et al, 2019), we show that TDP-4-bound transposon transcripts are de-silenced in human cells and demonstrate that these same targets are de-silenced in a subset of human ALS patients. Additional mechanisms for transposon de-silencing in ALS patients with C9orf72 repeat expansions have been suggested (Pereira et al, 2018;Prudencio et al, 2017;Zhang et al, 2019), although we note that C9orf72 status was not strongly associated with the ALS-TE group in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…Among the RBPs screened in this study, only Staufen was identified as a dsRBP. This is a significant point, because what most distinguishes Staufen from other RBPs screened is its ability to bind to dsRNA [34], a toxic byproduct of disrupted heterochromatin caused by PR toxicity [14] and nuclear loss of TDP-43 [13, 23, 24]. In this study, we showed that V5-PR36 expression led to increased co-localization of Staufen with heterochromatin and that degrading RNAs via RNase led to decreased nuclear accumulation of Staufen.…”
Section: Discussionmentioning
confidence: 73%
“…Next, we asked how PR toxicity might induce nuclear accumulation of dsRNA in C4 da neurons. Recent studies showed that loss of nuclear TDP-43, a prominent pathological feature of C9-ALS/FTD [22], can derepress RE transcription from heterochromatin [13, 23, 24], leading to accumulation of dsRNA in the nucleus. Thus we tested whether decreasing the amount of nuclear TBPH, a Drosophila ortholog of TDP-43, is sufficient to increase accumulation of Staufen in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Es por ello que su empleo en patologías complejas resulta de gran utilizad, como en el caso de la ELA, una enfermedad neurodegenerativa que se caracteriza por la progresiva disminución y atrofia de masa neuromuscular debido a la pérdida de motoneuronas (MN) [2], del tronco espinal y del cortex motor [3]. Como ocurre en este tipo de enfermedades, los mecanismos moleculares que dan lugar a esta neurodegeneración no están claramente definidos en la actualidad.…”
Section: Introductionunclassified
“…En condiciones fisiológicas, TDP-43 presenta una localización nuclear y se encuentra regulando muchas y diversas funciones implicadas en el procesamiento del ARN. En esta enfermedad disminuye su localización nuclear y se acumula en el citoplasma en forma de agregados [2]. En concreto aparece ubiquitinada e hiperfosforilada formando cuerpos de inclusión en el citoplasma de neuronas de la médula espinal de pacientes con ELA, pero también se ha detectado en pacientes con otras enfermedades neurodegenerativas como son la demencia frontotemporal y la enfemedad de Alzheimer.…”
Section: Introductionunclassified